Pandangan Filsuf Muslim Dan Barat Tentang Filsafat Dan Sains Islam - Yuni Armayanti; Laila Afni Rambe (Tasamuh: Jurnal Studi Islam, 2025)
This paper examines the views of Muslim and Western philosophers on Islamic philosophy and science, with the aim of understanding the contributions and interactions between the two traditions of thought. Muslim philosophers such as Al-Farabi, Ibn Sina, and Al-Ghazali attempted to integrate religious teachings with rational thought, creating a dialogue between revelation and reason. They emphasized the importance of empirical experience, ethics, and spirituality in the development of science. Western philosophers, on the other hand, provided a different perspective, often emphasizing rationalism, empiricism, and the scientific method. Despite differences in epistemological and methodological approaches, the dialogue between Muslim and Western philosophers shows that the search for truth is a universal endeavor that transcends cultural and religious boundaries. This paper hopes to provide deeper insight into the relationship between philosophy and science in the Islamic context and the significant contributions made by thinkers from both traditions to the development of global science. The findings suggest that despite methodological differences, both Muslim and Western thinkers recognize the organic unity of philosophy and science in the Islamic tradition, as well as its relevance in addressing contemporary epistemological challenges.